2005
DOI: 10.5980/jpnjurol1989.96.617
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain Analgetic Efficacy of Intraurethral Instillation of Anesthetic Jelly in Rigid Cystoscopy for Men

Abstract: Intraurethral instillation of anesthetic jelly had no efficacy for reducing the pain during cystoscopy. Instillation of the jelly itself caused considerable pain, and it made pain and uncomfortable feelings after the examination worse. These results suggested that the instillation of anesthetic jelly before rigid cystoscopy in men might not be useful enough for reducing the uncomfortable feeling during the examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study of pain associated with cystoscopy, Matsuda et al. 16 reported that the pain score during insertion of the cystoscope was largest, followed by the first and second urination after cystoscopy, during the cystoscopy itself, injection of gel, and urination the day after cystoscopy. As is very similar to the findings by Matsuda et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of pain associated with cystoscopy, Matsuda et al. 16 reported that the pain score during insertion of the cystoscope was largest, followed by the first and second urination after cystoscopy, during the cystoscopy itself, injection of gel, and urination the day after cystoscopy. As is very similar to the findings by Matsuda et al.…”
Section: Discussionmentioning
confidence: 99%